If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 2 + -4 = 6 Reorder the terms: 2 + -4 + 3y = 6 Combine like terms: 2 + -4 = -2 -2 + 3y = 6 Solving -2 + 3y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3y = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 3y = 6 + 2 3y = 6 + 2 Combine like terms: 6 + 2 = 8 3y = 8 Divide each side by '3'. y = 2.666666667 Simplifying y = 2.666666667
| 8x=16x+24 | | 2(6-2y)+4y=12 | | -5(1+6r)=22 | | 60*60*0+1= | | 22+8p=5p+4(p+4) | | 130.00=.80x+18 | | -22+7c=-5(4c+6) | | 2x(2)+17x+35=0 | | 3x(9)=24 | | x/281=40/360 | | 2x+13-7+6x= | | -16=-3(6k+9) | | 23=2+8(r+5) | | -20=-9d-2d | | 4.2+7=2.8 | | 3p^2+24p=-105 | | 6x^2-13b=0 | | 3-3*6+3=-13 | | -6+8(1-2x)=27 | | 9y+8+7=-26 | | (x+5)2=(2x)2 | | -6x-6=7x+33 | | 4(3y+2)=-28 | | -.4x+25=0 | | 3y=155-2x | | 1-3y=3-4y | | 4w-3w+4=-4+7 | | 13x+72= | | a-12+5=-12 | | 6-9n+5n=16-90 | | 9*x=88 | | x+45=6x |